Trusting the Record - Clarke, K.; Hartswood, M.; Procter, R.; Rouncefield, M.; Slack, R. (Methods of Information in Medicine, 2003)
Objectives: This paper aims to contribute to a longstanding interest in documents and paperwork in healthcare work through an examination of everyday work with patient records in a clinic.Methods: An ethnographic study of record keeping practices in a deliberate self harm clinic was conducted to consider the role that document work plays in the development of trust in the routine social interactions of a working division of labor.Results and conclusions: Issues of trust are seen to play central roles within the complexities of organizational working and some consequent implications for the deployment and use of electronic medical record systems are considered.
Keywords: Trust; paperwork; affordances; electronic medical records